Abilities and the structure of the firm - Tobias Hiller (International Review of Economics, 2022)
In this paper, we enhance the production games approach introduced by Hiller (Manag Decis Econ 40(5):520–525, 2019) with aspects from a recent article by Morelli and Park (Games Econ Behav 96(1):90–96, 2016), to analyze how abilities of employees influence the structure and the wage scheme of the firm. The analysis is done within the framework of cooperative game theory. Concretely, we apply the coalition structure approach and the χvalue (Casajus in Games Econ Behav 65(1):49–61, 2009).
Keywords: C71; D21; J24; M52; 330; Production games; Abilities; Structure of the firm; χ reward function; Stability